"Constitution (Written or Unwritten)": Legitimacy and Legality in the Thought of John Rawls. (19th November 2018) - Michelman, Frank I.
Abstract: John Rawls proposed, as what he called "the liberal principle of legitimacy, " that coercive exercises of political power can be justified to free and equal dissenters when "in accordance with a constitution (written or unwritten) the essentials of which all citizens, as reasonable and rational, can endorse." Does "unwritten constitution" there refer to norms of constitutional import, but that subsist only as custom, not as law? To norms that subsist as common law but not as code law? To empirical regularities of political practice, as opposed to normative rules and standards? Which interpretation is best?